Resíduo desidratado de cervejaria na ração de coelhos em crescimento - Lima, Paula Joyce Delmiro de Oliveira (2016)
Two experiments were conducted, the first to determine the chemical and digestible energy of dried brewers grain (DBG) and the second to evaluate the effect of the inclusion of this ingredient in the feeding of growing rabbits on performance, carcass characteristics, meat quality and economic viability. For the digestibility assay a total of 28 males rabbits were used, White New Zealand x California, with 50 days of age with an initial weight of 1.400±0.100 kg, distributed on a completely randomized block design, with two treatments and fourteen replications, using the total of feces method. The treatments were: basal diet (BD) and ration test (RT) comprised 60% of basal diet and 40% dried brewers grain. The dried brewers grain showed 90.43% of dry matter, 37.94% of crude protein, 51.72% of neutral detergent fiber, 22.08% of acid detergent fiber, 8.06% of ether extract, 5.30% of mineral matters and 3371.24 kcal of digestible energy/kg. To test the performance, a total of eighty rabbits (40 males and 40 females), White New Zealand x California, in the period from 40 to 90 days of age, allocated in a completely randomized block design in a 5x2 factorial arrangement, considering five levels of inclusion of the DBG (0, 7, 14, 21 e 28%), and sex (male and female), with four replicates of two animals. No effects were observed on the performance, however, it was observed that the carcass weight decreased linearly, while the pâncreas weight increased, due to the higher level of inclusion of the DBG. The weight of the liver of animals fed with DBG over 14% was lower than in animals that received feed without this ingredient. There was no effect of treatments on quality characteristics of meat rabbits. No effects were observed on relation meat/bone and qualitative meat characteristics. Considering the lower cost value of feed and better economic efficiency and cost indexes, the DBG may be included up to 28% in growing rabbits diets.